Physiological evaluation of dietary supplementation of steroid hormones and alpha-tocopherol in broiler chicken - Cyel V Yohannan (Department of Veterinary Physiology, College of Veterinary and Animal Sciences, 2007)
Thirty two, day old broiler chicks of Vencob strain were divided into four groups containing eight chicks in each group as G-I (control), G-II, G-III, and G-IV (treatments) and reared under identical management conditions for a period of four weeks with standard broiler ration as per BIS (1992). From fourth to eighth week of age, birds of group G-I (control) fed with Standard broiler finisher ration, G-II fed with Standard broiler finisher ration + Ethinylestradiol and Levanorgestrel incorporated @ 66.3 mg & 331.5 mg respectively per 100 kg of feed, G-III fed with Standard broiler finisher ration + dl-α-tocopherol @ 25 g per 100 kg of feed and G-IV fed with Standard broiler finisher ration + dl-α-tocopherol @ 25 g and a combination of Ethinylestradiol and Levanorgestrel @ 66.3 mg & 331.5 mg respectively per 100 kg of feed. Birds were regularly monitored for clinical health status, feed intake and individual weight (weekly intervals). Blood samples (5 ml each) were collected with and without anticoagulant at fortnightly intervals from fourth week to the end of experiment and analysed hematological parameters, plasma protein profile, lipid profile, enzymatic activity such as gama glutamyltransferase (GGT), aspartate aminotransferase(AST), superoxide desmutase (SOD), catalase and lipid peroxidation and serum concentration of calcium, phosphorus, copper and iron were also analysed. Histomorphology of liver adrenal and breast muscles were conducted. Liver and breast muscles were analysed for enzymes as GGT, tissue peroxidation, and crude protein and ether extract. Data were analysed statistically with appropriate tools. Results obtained showed that dietary supplementation of ethinylestradiol+levanorgestrel and dl-α-tocopherol failed to elicit any noticeable influence on the growth and feed efficiency and mineral status (serum calcium, phosphorous, copper and iron levels) in the experimental birds. Ethinylestradiol+levanorgestrel supplementation significantly lowered (P<0.05) total erythrocyte count (TEC), haemoglobin (Hb) and volume of packed red cells (VPRC). Ethinylestradiol+levanorgestrel supplementation significantly (P<0.05) lowered the plasma concentration of total lipids, total cholesterol and LDL (birds of G-II group) while dl-α-tocopherol did not bring such an effect. Ethinylestradiol+levanorgestrel and dl-α-tocopherol either alone or in combination significantly increased the plasma high density lipoprotein (HDL) levels in birds from sixth to eighth week of age. Ethinylestradiol+levanorgestrel and dl-α-tocopherol alone or in combination caused reduction in plasma VLDL and triglyceride values. There was a lower level of ether extract in muscles of all the treatment groups compared with control. Liver from birds of ethinylestradiol+levanorgestrel treated birds (G-II) had lower fat accumulation in hepatocytes. Ethinylestradiol+levanorgestrel fed group G-II (P<0.05) had the highest and the birds of dl-α-tocopherol supplemented group G-III had the lowest plasma GGT and AST activity at sixth and eighth week of age. These effects might be due to the effects of ethinylestradiol+levanorgestrel on the biliary system resulting in an elevated enzyme activity in plasma. Similarly ethinylestradiol+levanorgestrel caused significant increase in GGT levels only in the liver of G-II birds while there was no such change in breast muscles. Dl-α-tocopherol alone (G-III) or when combined with ethinylestradiol+levanorgestrel (G-IV) caused a significant increase (P<0.05) in catalse activity while ethinylestradiol+levanorgestrel and dl-α-tocopherol alone (G-II and G-III respectively) or in combination (G-IV) also showed lowered lipid peroxidation which indicated a better antioxidant status. Predominant effect of ethinylestradiol+levanorgestrel was observed on the plasma lipid profile (reduction in the level of plasma total cholesterol, LDL, VLDL cholesterol) while, -tocopherol showed its antioxidant properties. However, ethinylestradiol +levanorgestrel caused the damage to the biliary system resulting in elevated levels of enzymes such as GGT and AST. Dietary supplementation of ethinylestradiol+levanorgestrel and dl-α-tocopherol failed to elicit much anticipated effect on growth and other performance indices.